Factors affect employee’s turnover intention in banking industry - Gee, Siew Kit; Liew, Chin Min (2018)
This research mainly is to focus on the factors that affect the turnover intention in banking industry. As nowadays the turnover has become a trend in almost all the industry. A high turnover in a company will not only affect the company overall performance but also affect the company in long run as the company unable to retain the talents. This paper mainly discuss the factors that will affect the turnover intention of the banking industry in Malaysia. In this research, a total 500 questionnaires been distributed and total 395 qualified respondents been collected. SPSS ver. 23 and PLS been used for the data processing and data analysis. The results showed that working environment, job enrichment, job stress could significantly affect the job satisfaction; while job stress and job satisfaction will significantly affect the turnover intention. The results also found that working environment and job stress have indirect effect on turnover intention. The managerial implications also listed in the research to provide insight for the user to understand what can be done to reduce their organization turnover intention. The limitations of the study and the recommendations are provided for the researchers to conduct future research.